Are riding club members willing to pay or work for an overall quality improvement? - Stephanie Kiefer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2014)
This study examines the willingness-to-pay (WTP) and the willingness-to-work (WTW) of German riding club members for an overall quality improvement. Therefore, German riding club members were asked via an online questionnaire. As far as the author knows, this study is the first to include the concept of WTW in the amateur sport context. The results show that on average the participants would be willing to pay exteuro117.39 and would be willing to work 30.39 hours per year if the quality were improved. An extrapolation comes to the result that all German riding club members together would be willing to pay exteuro65,619,848 and would be willing to work 17,593,800 hours. Compared with the current aggregated membership fees and mandatory working hours, the potential surplus is exteuro23,014,936 and 11,448,696 working hours. Moreover, the study can also determine factors that significantly influence the WTP and WTW. – – Die vorliegende Studie untersucht die Zahlungsbereitschaft und die Arbeitsbereitschaft von Reitvereinsmitgliedern für eine Verbesserung der Gesamtqualität. Dafür wurden deutsche Reitvereinsmitglieder anhand einer Onlineumfrage befragt. Nach dem Wissen der Autorin ist diese Studie die erste, die das Konzept der Arbeitsbereitschaft im Rahmen des Amateursports verwendet. Die Ergebnisse zeigen, dass die Reitvereinsmitglieder durchschnittlich dazu bereit wären, 117,39 Euro zu zahlen und 30,39 Stunden pro Jahr zu arbeiten, wenn die Qualität erhöht würde. Eine Hochrechnung kommt zu dem Ergebnis, dass alle deutschen Reitvereins-mitglieder zusammen bereit wären, 65.619.848 Euro zu zahlen und 17.593.800 Stunden zu arbeiten. Verglichen mit den aktuellen Mitgliedsbeiträgen und Pflichtarbeitsstunden ergibt sich somit ein potentieller Überschuss von 23.014.936 Euro und 11.448.696 Arbeitsstunden. Darüber hinaus kann die Studie Faktoren bestimmen, die einen signifikanten Einfluss auf die Zahlungsbereitschaft und Arbeitsbereitschaft haben.
Keywords: C83; D12; L31; L83; M31; 650